Exploring the Mechanism of Indigo Naturalis in the Treatment of Ulcerative Colitis Based on TLR4/MyD88/NF-κB Signaling Pathway and Gut Microbiota - Yang, Qi-yue; Ma, Le-le; Zhang, Chen; Lin, Jun-zhi; Han, Li; He, Ya-nan; Xie, Chun-guang (Frontiers in Pharmacology, 2021)
Background: Clinical trials have proven that indigo naturalis is a candidate drug for treating ulcerative colitis (UC), but its therapeutic mechanism is still unclear. Purpose: This study aimed to evaluate the protective effect and mechanism of indigo naturalis to treat mice with dextran sulfate sodium (DSS)-induced UC. Methods: DSS-induced UC mice were treated with indigo naturalis (200 mg/kg), indigo (4.76 mg/kg), and indirubin (0.78 mg/kg) for 1 week. The anti-UC mechanism of indigo naturalis was studied by pathological section, inflammatory factor, western blot, and 16S rRNA sequencing. Results: According to body weight change, disease activity index, and colon length, indigo naturalis had the strongest anti DSS-induced UC effect, followed by indirubin and indigo. Pathological section showed that indigo naturalis, indigo, and indirubin could reduce the infiltration of inflammatory cells, increase the secretion of intestinal mucus, and repair the intestinal mucosa. Indigo naturalis, indigo, and indirubin could reduce IL-1β,IL-6, and TNF-α by inhibiting TLR4/MyD88/NF-κB signal transduction. Indigo naturalis and indigo could also reduce IgA and IgG both in serum and colon tissue. In addition, indigo naturalis, indigo, and indirubin could adjust the gut microbiota structure of DSS-induced UC mice, reducing the ratio of Firmicutes/Bacteroidetes and increasing the abundance of probiotics. Conclusion: Indigo and indirubin are one of the main anti-UC components of indigo naturalis. INN could regulate intestinal flora, reduce inflammation, repair intestinal mucosa, and improve the physiological status of DSS-induced UC mice and its anti-UC mechanism may be involved in inhibiting TLR4/MyD88/NF-κB signal transduction.